The Proportion of Undergraduates in Social Media KKU Group Who Were Knowledgeable of Condom Usage - Domrongsiri, Kawin; Somchai, Khwangamol; Siripongsatian, Dheeratama; Treewiriyanuphab, Benjarat; Thongsaen, Phaosin; Jandaboot, Kattareeya; Wongcha, Nutchanon; Leelerdyudth, Rawikarn; Sopunna, Kittiphon; Karaket, Panusart; Bumrerraj, Sauwanan; Kanato, Manop (ศรีนครินทร์เวชสาร, 2015)
Background and objective: The accurate condom usage can prevent unwanted pregnancy and sexual transmitted disease effectively but 18% of users misuse it. In addition, Facebook users in Thailand had reached the 3rd rank in ASEAN, so we assumed that online questionnaires might be a new interesting route for data collection. This study aimed to assess the proportion of undergraduates in social media KKU group who were knowledgeable of condom usage. Methods : This was a descriptive study at Khon Kaen university. 604 undergraduate students who were a member of KKU group during November 2014 were selected by accidental sampling. A link to a self-administered online questionnaire was posted and reposted in the social media group webpage. It included 1) demographic information 2) knowledge of condom usage 3) preferred responding route of questionnaire. SPSS-PC v.17 was used to analyze descriptive statistic. Results: 604 members completed the survey. 80.1% of respondents were undergraduates students and 69.6% of them had accuracy knowledge of the condom usage. 93.5% of them preferred online questionnaire to provide the information about sex education, 3.7% preferred paper questionnaire and 2.8% preferred direct interview. Conclusion: 69.6% of undergraduate students were knowledgeable about the condom usage. Most of them preferred to provide information about sex education via online questionnaire.